Lucky Switcheroo: Dramatic Potency and Selectivity Improvement of Imidazoline Inhibitors of Human Carbonic Anhydrase VII - Kalinin, Stanislav (ACS Med Chem Lett, 2017)
[Image: see text] A substantial improvement of potency and selectivity of imidazoline-based inhibitors of hCA VII (a promising target for the treatment of seizures and neuropathic pain) was achieved by simply switching the position of the benzenesulfonamide moiety from N(1) (as in the earlier reported series) to C(2). Selectivity indices vs the off-target isoforms (hCA I, I, I and IV) greater than 100 were reached, which is exceedingly rare for hCA VII inhibitors. The drastic profile improvement of the new series has been rationalized by an additional hydrogen bonding with the nonconserved Q69 residue in the active site of hCA VII (absent in the other three isoforms studied), which also results in a favorable accommodation of the inhibitor’s lipophilic periphery in the nearby hydrophobic pocket. The robustness of the docking simulations was tested and confirmed by molecular dynamics simulations.